Developing a Core Set of Outcome Measures for Behcet Disease: Report from OMERACT 2016 - (:unkn) unknown (J RHEUMATOL PUBL CO, 2017)
Objective. The Outcome Measures in Rheumatology (OMERACT) Vasculitis Working Group has been working toward developing a data-driven core set of outcome measures for use in clinical trials of Behcet's syndrome [Behcet disease (BD)]. This paper summarizes the group's work through OMERACT 2016, discussions during the meeting, and the future research agenda. Methods. Qualitative patient interviews were conducted among 20 patients with BD who have different types of organ involvement. A 3-round Delphi among BD experts and patients was initiated to identify domains, subdomains, and outcomes to be assessed in clinical trials of BD. The results of these studies were discussed during OMERACT 2016 and next steps were planned. Results. Patients' perspectives and priorities were identified through qualitative interviews that identified candidate domains and subdomains for inclusion in the Delphi and characterized some shortcomings of the currently used patient-reported outcomes in BD. The first round of the Delphi was completed and several domains or subdomains were endorsed by the experts and/or the patients. Because many more items were endorsed than would be feasible to assess during a clinical trial, rating and ranking of items by physicians and patients was planned as a next critical step. The challenges of assessing specific organ system involvement was also discussed. Conclusion. The OMERACT Behcet Syndrome Working Group research program will identify core domains for assessment in BD with the goal of developing a core set of outcome measures for use in all trials of BD with the option to incorporate additional outcomes for specific organ involvement.
Keywords: BEHCET DISEASE; OUTCOMES; OUTCOME MEASURES; OUTCOME ASSESSMENT; OMERACT; CONSTANT COMPARATIVE METHOD; CLINICAL-TRIALS